The severity of adverse events is associated with the age of hospitalized patients: a retrospective study - Goicochea Palomino, Anabela Eliane (2023)
Background: Adverse events (AE) are unintentional injuries or harm that occur during medical care. These represent a public health problem, and they are one of the main causes of death in the world. Objective: The objective of the study was to determine AEs derived from nursing care in hospitalized patients, as well as to estimate their frequency according to severity, follow-up, and type of care service. Methods: We undertook a retrospective study in hospitalized patients. EA by severity (no damage, irreversible damage, disability, and death), types (pressure ulcers (PUs), falls, phlebitis, and blood transfusion), and demographic data (age and gender) were taken into account. Damage severity was determined according to the guidelines of the Peruvian Ministry of Health. Results: We obtained 127 reports (55.9% women, mean age of 28+8 years). The main EA were PUs (57.5%), followed by phlebitis (20.5%) and falls (19.7%). Most of the AEs have been followed up, and almost all the AEs occurred during hospitalization. In addition, being older was associated with AE severity (p=0.002), as there were reports of 2 (1.6%) cases of death, and half of the cases resulted in the disability of patients > 48 years old. Conclusion: PUs were the most frequent AE. They affected younger patients, and their severity was associated with older age. It is important for health professionals to recognize and notify AEs in order to ensure the patients’ well-being; also, health institutions needs to be encouraged for improving their risk reduction programs.